Analisis Peran Tenaga Ahli P3MD Dalam Pengawasan dan Pengendalian Penggunaan Dana Desa Pada DPMN Kabupaten Pasaman Barat - Anggela Tamara; Aqwa Naser Daulay (Yayasan Daarul Huda Kruengmane, 2023)
This research aims to analyze the role of experts P3MD in monitoring and controlling the use of village funds in the DPMN of West Pasaman Regency. The method used in this research is a qualitative research method based on secondary data. Secondary data was collected using various interview techniques, observation, document analysis. Where the subject of the information is community self-help borers. Village funds have an important role in supporting economic and social development in rural areas, but are also vulnerable to misuse which can harm local communities. The results of this research show that the role of experts P3MD is very important in monitoring village funds. Ekperts P3MD's ability to identify violations can trigger necessary corrective actions and ensure more efficient and effective use of village funds.